Call to action: Understanding the differences in the use of SGLT-2 inhibitors and GLP-1 receptor agonists - Apurva Khedagi; Cara Hoke; Michelle Kelsey; Andrea Coviello; W. Schuyler Jones; Larry R. Jackson, II; Manesh R Patel; Rob W. McGarrah; Neha J Pagidipati; Nishant P. Shah (Elsevier, 2023)
Cardiovascular disease remains one of the most prominent global health problems and has been demonstrated to disproportionally affect certain communities. Despite an increasing collective effort to improve health inequalities, a multitude of disparities continue to affect cardiovascular outcomes. Among the most prominent disparities within cardiovascular disease prevention are with the use and distribution of sodium-glucose cotransporter-2 (SGLT-2) inhibitors and glucagon-like peptide 1 (GLP-1) receptor agonists. Several landmark trials have demonstrated the efficacy of these novel agents, not only in cardiovascular disease prevention among those with diabetes, but also in heart failure and chronic kidney disease. However, the use of these agents remains limited by disparities in certain racial/ethnic, sex, and socioeconomic groups. This review works to highlight and understand these differences on the use and prescribing patterns of pivotal agents in cardiovascular disease prevention, SGLT-2 inhibitors and GLP-1 agonists. Our aim is to enrich understanding and to inspire efforts to end disparities in cardiovascular morbidity and mortality due to race, sex and income inequality.